Fatigue crack paths under the influence of changes in stiffness - G. Kullmer; B. Schramm; H. A. Richard (Fracture and Structural Integrity)
An important topic of the Collaborative Research Centre TRR 30 of the Deutsche Forschungsgemeinschaft (DFG) is the crack growth behaviour in graded materials. In addition, the growth of cracks in the neighbourhood of regions and through regions with different material properties belongs under this topic. Due to the different material properties, regions with differing stiffness compared to the base material may arise. Regions with differing stiffness also arise from ribs, grooves or boreholes. Since secure findings on the propagation behaviour of fatigue cracks are essential for the evaluation of the safety of components and structures, the growth of cracks near changes in stiffness has to be considered, too. Depending on the way a crack penetrates the zone of influence of such a change in stiffness and depending on whether this region is more compliant or stiffer than the surrounding area the crack may grow towards or away from this region. Both cases result in curved crack paths that cannot be explained only by the global loading situation. To evaluate the influence of regions with differing stiffness on the path of fatigue cracks the paths and the stress intensity factors of cracks growing near and through regions with differing stiffness are numerically determined with the program system ADAPCRACK3D. Therefore, arrangements of changes in stiffness modelled as material inclusions with stiffness properties different from the base material or modelled as ribs and grooves are systematically varied to develop basic conclusions about the crack growth behaviour near and through changes in stiffness.